PERAN PENGURUS ASRAMA DALAM PENGELOLAAN LINGKUNGAN BELAJAR DI YAYASAN PONPES SAFINATUL HUDA SURABAYA - Farizin, Nizar; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research is a descriptive qualitative study that purpose to describe the role of the hostel manager in the Safinatul Huda Surabaya Pondok Pesantren in the management of hostel learning environment. A boarding house is a form of institution that organizes educational programmes through non-formal education units, which supports lifelong education on Islamic religious education services. The dormitory is a lodging place for the mourners as a means of study, activity, and rest. The dormitory is a real learning environment for the centurion, so it requires governance. The management of a hostel environment is carried out by the hostel manager as the manager of the study environment. The study took all members of the hostel of 7 (seven) people as the primary source of data that is thought to be able to explain the circumstances, as well as the social atmosphere at the site of the study, that is, a hostel. Supported by documentation and observation results, such documents and observations are comparative data for the validation of primary data. The results of the research show that the role of the manager in the management of space utilization is considered less effective in the utilization of the function of the room. A contributing factor to sustainable environmental maintenance is central involvement in space and equipment maintenance activities. The role of the hostel manager in environmental control is less efficient and less communicative in the handling of hostels that violate hostel environmental order. The availability of incomplete management instruments on learning environmental management becomes a major obstacle in social environmental control.